Similarities and Differences in Buddhist-Christian Dialogue During the Late Ming-Early Qing and Late Qing-Early Republican Eras - HE, Zhiren (Journal of Research for Christianity in China (JRCC), 2025)
The late Ming and early Qing Dynasty and the late Qing and early The Republic of China Dynasty are two important periods of Buddhist and Christian ’ dialogue in China, which take an important significance in China’s history of religious dialogue. To understand the overall situation about their consistency and differences between each other can help us to better understand the development course of studying dialogue in the history of our country the expansion and development, and guide the current religious dialogue. The late Ming and early Qing Dynasty and the late Qing Dynasty, the two members of the organization, studying the dialogue in the historical background, development mode, starter, expand the content of many aspects of the existing consistency is very amazing, there are also many differences need to pay attention to. Many of ideologist and religious activists such as Matteo Ricci‎, Timothy Richard, Karl Reichelt, Master Taixu emerged in this time, who worthy of our mind. The innovative and important ideas they put forward are worthy of our careful study.